Sinar Harian, 22 Februari 2008 - [author not identified] (Selangor Karangkraf Sdn Bhd, 2008)
In June 1992, a total of 178 Heads of State (including Malaysia) attending the Conference Peak of the Earth United Nations at Rio De Janeiro, Brazil